Generation of Mature Monocyte-Derived Dendritic Cells in the Presence of Heparin and Monocyte Conditioned Medium: Phenotypic and Functional Comparison - Delirezh, Nowruz (Pasteur Institute of Iran, 2011)
Background: Dendritic cells (DC) induce tumor or pathogen-specific T cell responses in humans. Several laboratories have developed culture systems, including maturation factors for human DC from peripheral blood monocytes. We comprehensively compared standard maturation stimulus, an autologous monocyte-conditioned medium (MCM), with heparin for their ability to promote uniformly mature DC that elicit T cell responses. Methods: A short (4-day) priming of plastic adherent monocytes with granulocyte-macrophage colony stimulating factor (GM-CSF) and IL-4 with or without heparin was followed by 48-hour incubation in MCM to generate fully mature and stable DC. Phenotypic and functional analyses were carried out using anti-CD14 and anti-CD83 monoclonal antibodies, and mixed lymphocyte reaction, respectively. Results: We found that fully matured DC with a large amount of cytoplasm and copious dendritic projections were visible at the end of culturing period in the presence of MCM, heparin and MCM plus heparin. Thus, DC generated with these maturation factors are non-adherent and have typical satellite morphology. Flow cytometric analysis using anti-CD14 (monocyte marker) and anti-CD83 (mature DC marker) revealed that expression of CD14 decreased in MCM plus heparin-treated DC, and the expression of CD83 was increased when heparin and MCM used as a maturation factor. Functionally, MCM and MCM plus heparin-treated DC showed stronger mixed leukocyte reaction than heparin alone. Conclusion: These results support the use of the MCM with heparin as maturation factor that could result in functionally mature monocyte-derived DC in comparison to either MCM or heparin alone.